Gambaran kualitas hidup dan prestasi akademik pada siswa SMA Negeri 9 Manado di masa pandemi COVID-19 - Rogi, Joanne K. F.; Rombot, Dina V.; Siagian, Iyone E. T. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2020)
Background: Adolescents are the population who fall into the 10-19 age group and in this phase, there is rapid growth and development. High school students are individuals who belong to the youth group and their job is to learn to achieve academic achievement. The emergence of the COVID-19 outbreak resulted in students learning from home. This can affect the quality of life of adolescents. Quality of life is the perception of individuals in their lives in terms of cultural contexts, behavior and value systems and is related to the standard of living, expectations, pleasures, and individual assessments of their position in life. This study aims to describe the quality of life and academic achievement of SMA Negeri 9 Manado students during the COVID-19 pandemic. Methods: This was a descriptive study on 95 adolescents who have academic achievements.Results: The majority of adolescents have a moderate level of quality of life. Students who have higher average scores (score of 90.6-100) have a higher quality of life (physical, psychological, social, and environmental health domains) than students with lower scores (score of 74,6-90,5)Conclusion: Students of SMA Negeri 9 Manado have good academic achievements and a moderate level of quality of life. The higher academic achievement the higher the quality of life of these students.Keywords: Adolescents, quality of life, academic achievement